Role of phase change materials in thermal energy storage : Potential, recent progress and technical challenges - Samykano, Mahendran (Elsevier Ltd, 2022)
Thermal energy storage (TES) using phase change materials (PCM) have become promising solutions in addressing the energy fluctuation problem specifically in solar energy. However, the thermal conductivity of PCM is too low, which hinders TES and heat transfer rate. In recent days thermally enhanced PCMs are a promising candidate for TES and heat transfer applications. This research designates the review on various thermal conductivity and heat transfer enhancement techniques of PCMs like, increasing the heat transfer area, use of various highly conductive porous foam materials (copper, aluminium, nickel, graphite, and carbon), mix of materials, use of multiple PCM and nano dispersed PCM (Copper oxide (CuO), Aluminium dioxide (Al2O3), Carbon nanotubes (CNTs), graphene, etc.). Also, the long-term stability, phase segregation and super colling are extensively discussed. Furthermore, energy storage applications of highly conductive PCMs in advanced fields like solar thermal system, desalination units, pharmaceutical industry, fabrics, food processing, battery thermal management etc are discussed. It has been observed that porous materials/foam dispersed PCM had better heat transfer/storage capacity (thermal conductivity 2–500 times more). In addition, organic PCMs have been widely used, due to its long-term stability, low or no supercooling, less or no corrosion, and recyclability. The highly stable thermally enhanced PCMs are used for long-term TES/heat transfer applications.